Análise de textura e propriedades magnéticas em aços maraging 300 e 350 em várias condições de tratamento - Silva, Jean Jefferson Moraes da (2005)
Maraging steels are Ni-Co-Mo-Ti ultra-high resistant steels used in special applications from military and nuclear applications to aircraft components, pressure vessels and sport equipment. Nowadays some investigations have being made in the application of these steels as high resistance magnetic materials. Maraging steels present some advantages when compared to other kinds of steels and alloys. They present extremely high mechanical strength, great conformability in the solution treated state and good capacity of strengthening by aging. The use in histeresys motors is one of the applications why magnetic properties of these steels are being investigated. For this purpose, the material must have, beyond high mechanical strength, typical characteristics of soft or semi-hard magnetic materials. The magnetic properties are presented and discussed with the aim of establishing the best mechanical and heat treatments for magnetic application. Texture analysis were performed and discussed with the aim of presenting the material texture that fits the easiest magnetization direction. The phase quantifications for all different conditions of termomechanical treatment were performed by X-ray diffraction. The results were used to determine the influence of austenite in texture, mechanical strength and magnetic properties of the material. Mechanical properties of the material were estimated by hardening tests. The analysis of the results showed that almost all samples have the same texture components and the <100> easy axes of magnetization are located in the sheet’s plane at an angle of 45º to the rolling direction. The magnetic properties showed that all samples have minimum requisites for using in histeresys motors, being the intermediate solution annealed samples the worst condition and the nitrogen cooled samples the best indicated for this kind of application.